2020
DOI: 10.1002/jcp.29732
|View full text |Cite
|
Sign up to set email alerts
|

The effector cells and cellular mediators of immune system involved in cardiac inflammation and fibrosis after myocardial infarction

Abstract: The cardiac repair after myocardial infarction (MI) involves two phases, namely, inflammatory response and proliferative response. The former is an inflammatory reaction, evoked by different kinds of pro‐inflammatory leukocytes and molecules stimulated by myocardial necrosis, while the latter is a repair process, predominated by a magnitude of anti‐inflammatory cells and cytokines, as well as fibroblasts. Cardiac remodeling post‐MI is dependent on the balance of individualized intensity of the post‐MI inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…It is clear that MI is a cardiovascular disease, and the repair process of myocardial tissue after MI is completed by scar repair. In addition to the early occurrence of cardiomyocyte apoptosis, necrosis and inflammation, cell proliferation and migration play a vital role in the repair process of myocardial tissue [49] . Many studies have shown that cancer is associated with increased risk and poor prognosis of MI [50] , [51] , [52] .…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that MI is a cardiovascular disease, and the repair process of myocardial tissue after MI is completed by scar repair. In addition to the early occurrence of cardiomyocyte apoptosis, necrosis and inflammation, cell proliferation and migration play a vital role in the repair process of myocardial tissue [49] . Many studies have shown that cancer is associated with increased risk and poor prognosis of MI [50] , [51] , [52] .…”
Section: Discussionmentioning
confidence: 99%
“…The deposition of ECM causes an increase in the stiffness of the heart and a decrease in compliance, which affects the normal diastolic and contractile functions of the heart ( Frey and Olson, 2003 ). It is currently believed that the pathogenesis of cardiac fibrosis involves multiple influencing factors, including the endothelial-to-mesenchymal transition (EndMT), left ventricle pressure overload, inflammation activation, the effector cells and cellular mediators of immune system in cardiac tissue ( Burke et al, 2019 ; Martinez-Martinez et al, 2019 ; Liu et al, 2020 ; Wilhelmi et al, 2020 ).…”
Section: Effects Of Higenamine On Heart Disease In Vivomentioning
confidence: 99%
“…Cardiomyocyte hypertrophy is crucial in pathological heart remodeling as well as HF. Zhu et al ( Liu et al, 2020 ), investigated the effect of higenamine on cardiomyocytes hypertrophy in adult mouse cardiac myocytes (AMCM) in vitro . Studies have found that higenamine has no significant effects on the cardiomyocytes hypertrophy induced by PE, but it could dose-dependently inhibit the relative mRNA and protein expression of α-SMA in TGF-β1 stimulated neonatal rat cardiac fibroblasts (NRCF).…”
Section: Effects Of Higenamine On Heart Disease In Vitromentioning
confidence: 99%
“…MI progression involves complex interactions among cardiomyocytes, non-cardiomyocytes, and other cell types ( 4 ), including fibroblast activation, immune cell infiltration, angiogenesis. MI repair comprises the inflammatory, proliferative, and mature stages ( 5 ) ( Figure 1 ). Identifying the changes in myocardial cell function, transcription factors, and the molecular pathways associated with the foregoing cellular processes may facilitate the development of novel therapeutic strategies ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…MI repair comprises the inflammatory, proliferative, and mature stages ( 5 ) ( Figure 1 ). Identifying the changes in myocardial cell function, transcription factors, and the molecular pathways associated with the foregoing cellular processes may facilitate the development of novel therapeutic strategies ( 5 , 6 ). The multifactorial nature of MI renders study design and interpretation very difficult.…”
Section: Introductionmentioning
confidence: 99%